Notary Accountability for False Information by Appellant in Establishment Deed of Limited Liability Company - Achmad Gunawan (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2021)
The purpose of this research is to analyze and find out: 1). Procedure for Making a Deed of Registration of a Limited Liability Company. 2). The form of the Notary's liability for the deed of establishment of a Limited Liability Company made based on false information. The approach method in this research is normative juridical. The data used are primary and secondary data obtained through interviews and literature study, data analysis was carried out by analytical descriptive. The results of the research concluded: 1). The procedure for making the registration deed of a Limited Liability Company (PT) is that it must meet the requirements in an establishment of a PT other than what has been regulated in Article 7 paragraph (1) of the Company Law, which must be based on an agreement made by 2 (two) or more persons, the form of the Deed of Establishment of a PT must also be in the form of a Notary Deed drawn up in the Indonesian language, in other words, in this case the Notary has the role of making a Deed of Establishment of a PT, which functions as probationis causa and solemnitas causa. 1) The notary is only formally responsible for the documents shown to him, in which the notary has no obligation to materially prove the truth of the documents shown to him. However, the notary must conduct an examination of all documents submitted to him which then also asks the appearer for information to be synchronized with the information contained in the document, in which case there are irregularities related to the documents and information submitted to him, the notary may refuse to continue the stages of making the deed. . Notaries can only be held accountable if the Notary is proven to have violated the provisions of Articles 84 and 85 of the UUJN and the notary code of ethics, which can be held criminally, civilly and administratively responsible.